Late Pleistocene to Holocene glacio-eustatic history as recorded in the Pescara paleovalley system (Central Italy, Adriatic basin). (November 2022) - Campo, B.; Barbieri, G.; Di Martino, A.; Hong, W.; Scarponi, D.; Vaiani, S.C.; Amorosi, A.
Abstract: A buried paleovalley system, about 50 m deep and 2 km wide, is documented from the Pescara coastal plain. Based on stratigraphic, sedimentological, paleontological, chronological and geotechnical data, the paleovalley profile and 3D facies architecture of the paleovalley fill (PVF) were reconstructed. The lowermost PVF is a laterally extensive fluvial gravel body, up to 13 m-thick, that represents the lowstand systems tract (LST; pre-11.3 ka cal BP). Above lowstand deposits, the transgressive systems tract (TST), 21 m-thick, shows a deepening-upward trend, from freshwater/inner-estuarine to brackish/outer-estuarine facies associations (11.3–8.0 ka cal BP). The upper part of the succession (highstand systems tract – HST) shows a shallowing-upward tendency from paludal to fluvio-deltaic deposits. Seven millennial-scale parasequences (Ps) were identified within the Pescara Holocene (TST + HST) succession. Transgressive Ps1-3 exhibit a distinctive retrogradational stacking pattern. Highstand Ps4-7 are aggradationally-to-progradationally stacked. During the aggradational phase (P4), the estuary was gradually filled and swamp environments spread onto the valley interfluve. Because of subsequent progradation (Ps5-7), delta plain conditions established. In the research core, TST parasequences show higher accumulation rates (up to 9.4 mm/y) than HST ones (1.3–1.8 mm/y). Thus, the study area evolved from a region of sediment storage (11.3–8.0 ka cal BP) into a sector of prevalent sediment bypass (last 8.0 ky). Major early Holocene flooding events were possibly triggered by Melt-Water Pulses (MWPs) 1B, 1C and 1D. The eustatic rise linked to MWP-1B reasonably caused the P1 flooding event (11.3 ka cal BP). Post-MWPs 1C and 1D sea-level rises likely provoked the complete drowning of the paleovalley system and the subsequent maximum landward migration of the shoreline (about 8.0 ka cal BP). This study provides new evidences, in terms of sedimentary response, of the poorly-documented MWPs 1C and 1D, and the first documentation of MWP-1B eustatic effects in an onshore sector of the Central Adriatic. Highlights: A buried paleovalley system (PVS) was recognized below the Pescara coastal plain. Facies architecture resembles the one documented for several PVSs worldwide. Seven millennial-scale parasequences form the Holocene succession. Glacio-eustasy was the major controlling factor during the post-LGM transgression. The Pescara valley fill provides evidence for melt-water pulses 1B, 1C and 1D.